2017
DOI: 10.1002/chem.201700971
|View full text |Cite
|
Sign up to set email alerts
|

Folding Topology of a Short Coiled‐Coil Peptide Structure Templated by an Oligonucleotide Triplex

Abstract: The rational design of a well-defined protein-like tertiary structure formed by small peptide building blocks is still a formidable challenge. By using peptide-oligonucleotide conjugates (POC) as building blocks, we present the self-assembly of miniature coiled-coil α-helical peptides guided by oligonucleotide duplex and triplex formation. POC synthesis was achieved by copper-free alkyne-azide cycloaddition between three oligonucleotides and a 23-mer peptide, which by itself exhibited multiple oligomeric state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 62 publications
1
23
1
Order By: Relevance
“…The programmed self‐assembly of oligonucleotides (ONs) through hydrogen bond and π‐stacking interactions has inspired the burgeoning development of elaborate two‐ and three‐dimensional DNA nanostructures during the last decades . With sizes ranging from nano‐ to micrometers, the user‐defined geometry and the facile chemical functionalization of DNA nanostructures offer ideal nanoscale molecular construction tools for peptide and protein engineering with unparalleled spatial accuracy down to the ångström‐scale level with various chemical and biological applications as long term goals . However, only a few examples have demonstrated bottom‐up construction of artificial protein mimics using the programmability and adaptability of nucleic acid secondary structures, including DNA triplexes, G‐quadruplexes and multiple DNA junctions .…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…The programmed self‐assembly of oligonucleotides (ONs) through hydrogen bond and π‐stacking interactions has inspired the burgeoning development of elaborate two‐ and three‐dimensional DNA nanostructures during the last decades . With sizes ranging from nano‐ to micrometers, the user‐defined geometry and the facile chemical functionalization of DNA nanostructures offer ideal nanoscale molecular construction tools for peptide and protein engineering with unparalleled spatial accuracy down to the ångström‐scale level with various chemical and biological applications as long term goals . However, only a few examples have demonstrated bottom‐up construction of artificial protein mimics using the programmability and adaptability of nucleic acid secondary structures, including DNA triplexes, G‐quadruplexes and multiple DNA junctions .…”
Section: Introductionsupporting
confidence: 67%
“…We relied on our previous POC synthesis strategy, such that the bioconjugations between bicyclo[6.1.0]nonyne (BCN)‐functionalized ONs and azide‐modified peptides were accomplished via copper‐free ring‐strain promoted azide‐alkyne cycloaddition (Figure ). All involved ONs were synthesized from commercially available d ‐nucleoside or mirror‐image l ‐nucleoside monomers via phosphoramidite chemistry and standard automated DNA synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNAs are inherently charged and hydrophilic; however, peptides can have a wide variety of charge states and polarity characteristics depending on their primary sequences. Although quite a few studies on POCs have been reported, there is still limitations in the synthesis of POCs containing peptides with different properties for the following reasons: First, chemical incompatibility exists in the solid‐phase synthesis for DNAs and peptides. This is especially true during the final step of solid‐phase synthesis; DNAs are normally deprotected and cleaved from the solid support in basic conditions, while peptides are cleaved in acidic condition.…”
Section: Introductionmentioning
confidence: 99%